Calibrations of the FDS Long Counter for Neutron Fluence Measurement. (1st February 2018) - Hong, Bing; Liu, Chao; Li, Taosheng; Wang, Yongfeng; Li, Yanan; Mazunga, Mohamed
Abstract: Long counters are widely used for monitoring neutron fluence owing to their constant response in a wide energy range. In this study, an extended long counter named FDS-LC (FDS Long Counter), having a flat response over a wide neutron energy range from 1 keV to 20 MeV, was developed to monitor high neutron fluence. The geometry and basic structure of FDS-LC was optimized by using Monte Carlo simulations, and it consists of the BF3 thermal neutron counter, the inner and outer polyethylene moderators, borated polyethylene absorption layer, and chromium and lead metal neutron multiplier. The parameters such as the effective center, the energy response, and the angluar response of the FDS-LC were estimated using Super Monte Carlo code. The experimental validation of these parameters were performed by using 241 Am-Be source and T(d, n) 3 He neutron source at the China Institute of Atomic Energy in Beijing. The results showed that the fluctuation of the response in the energy range from 1 keV to 20 MeV was less than 12% and the effective center positions were approximately equal to   6.694 + 0.374 × E n M e V . The comparison of the simulation and experimental results of the angular response function showed good agreement with a maximum deviation less than 15.7%.